PENGARUH KOMITMEN PROFESI DAN SELF-EFFICACY TERHADAP KONFLIK PERAN - Sopiyan , Pipih; Abdul Aziz , Haris (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2019)
This research was carried out on employees of the Regional Office of the Rural Bank of Majalengka. The purpose of this study was to find out how the influence of professional commitment and Self-efficacy on role conflict in employees of the Regional Public Housing Agency of the Central Majalengka both partially and simultaneously. This study uses a survey method with a descriptive and verification analysis approach. The populations in this study were all employees of the Majalengka BPR Regional Regulation Office as many as 47 respondents.The results of the study show that professional commitment, self-efficacy on employees of the BPR Perumda Majalengka Center are in a very high category. While role conflict is in a very good category. Partially profession commitment does not significantly influence role conflict and self-efficacy has a significant positive effect on role conflict. Simultaneously professional commitment and self-efficacy have a positive and significant effect on role conflict.